The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/jid.2011.420
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet Endothelial Cell Adhesion Molecule-1 (PECAM-1/CD31) and CD99 Are Critical in Lymphatic Transmigration of Human Dendritic Cells

Abstract: The reverse transmigration (RT) of tissue-resident dendritic cells (DCs) across lymphatic endothelia is prerequisite for the initiation of adaptive immune responses and might be regulated in a manner similar to diapedesis. Specifically, CD31 and CD99, which act as gatekeepers during diapedesis, might have a role in RT of DCs. We found that human lymphatic endothelial cells (LECs) and DCs in vitro and in human skin explants express CD31 and CD99. In human skin, CD31 was enriched along intercellular surfaces of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 23 publications
(27 reference statements)
1
37
0
Order By: Relevance
“…The chemokine (C-C motif) ligand (CCL)21/chemokine receptor type (CCR)7 pathway is the major chemokine-signaling pathway for the entry of both T cells and DCs from the tissues into the lymphatic vasculature (Debes et al, 2005; Ohl et al, 2004; Saeki et al, 1999; Weber et al, 2013) (Figure 1a). The chemokine (C-X-C motif) ligand (CX3CL)1/CX3CR1 (Johnson and Jackson, 2013) and CXCL12/CXCR4 (Kabashima et al, 2007; Torzicky et al, 2012) pathways also appear to play a part in DC migration. Their role, however seems to be minor compared with that of CCL21/CCR7 and restricted to inflammatory conditions, in which application of tumor necrosis factor and haptens induces the expression of CX3CL1 and CXCL12 by LECs (Johnson and Jackson, 2013; Kabashima et al, 2007) (Figure 1a).…”
Section: Role Of the Lymphatic System In Tissue Maintenancementioning
confidence: 99%
“…The chemokine (C-C motif) ligand (CCL)21/chemokine receptor type (CCR)7 pathway is the major chemokine-signaling pathway for the entry of both T cells and DCs from the tissues into the lymphatic vasculature (Debes et al, 2005; Ohl et al, 2004; Saeki et al, 1999; Weber et al, 2013) (Figure 1a). The chemokine (C-X-C motif) ligand (CX3CL)1/CX3CR1 (Johnson and Jackson, 2013) and CXCL12/CXCR4 (Kabashima et al, 2007; Torzicky et al, 2012) pathways also appear to play a part in DC migration. Their role, however seems to be minor compared with that of CCL21/CCR7 and restricted to inflammatory conditions, in which application of tumor necrosis factor and haptens induces the expression of CX3CL1 and CXCL12 by LECs (Johnson and Jackson, 2013; Kabashima et al, 2007) (Figure 1a).…”
Section: Role Of the Lymphatic System In Tissue Maintenancementioning
confidence: 99%
“…Another adhesion molecule is FAT2, which is an integral membrane protein characterized by the presence of cadherin-type repeats and plays a role in the control of planar cell polarity (62). We also detected CD99, which has been described as expressed in immune cells and is a key mediator of the transendothelial migration of neutrophils and dendritic cells (63,64). We found orosomucoid (alpha1-acid glycoprotein), which is needed to maintain the high capillary permselectivity required for normal homeostasis.…”
Section: Discussionmentioning
confidence: 78%
“…PECAM-1 is unlikely to play a role in S. Typhimurium entry into M cells, as previous studies have shown an absence of PECAM-1 expression on in vitro cultured M-cell-like cells (25). However, PECAM-1 is expressed on the surfaces of macrophages and dendritic cells and thus may be important in interaction with these host cells (15,34). Uptake of S. Typhimurium is enhanced by opsonization with antibodies through Fc receptor-mediated phagocytosis, but it is thought that other receptors on host cells also play a role in internalization.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, our data showed reduced dissemination of Salmonella from the gastrointestinal tract into systemic organs in the absence of PECAM-1. PECAM-1 was shown to be essential for human dendritic cell migration through the lymphatics, and it is thus likely that PECAM-1 is involved in dendritic cell trafficking (34). No differences in the number of CD11c ϩ cells in the spleens of naive and infected PECAM-1 Ϫ/Ϫ mice in comparison with wild-type mice have been reported, and the antigen-presenting capacities of cultured dendritic cells of PECAM-1 Ϫ/Ϫ and wild-type mice are comparable (28).…”
Section: Discussionmentioning
confidence: 99%